Utilization of telehealth by surgeons during the COVID 19 pandemic in Australia: lessons learnt. Issue 4 (26th February 2021) - Wiadji, Elvina; Mackenzie, Lisa; Reeder, Patrick; Gani, Jonathan S.; Carroll, Rosemary; Smith, Stephen; Frydenberg, Mark; O'Neill, Christine J.
Abstract: Background: The COVID‐19 pandemic has led to the rapid and widespread adoption of telehealth. There is a need for more evidence regarding the appropriateness of telehealth, as well as greater understanding of barriers to its sustained use within surgery in Australia. Methods: A survey weblink was sent via email to 5558 Australian Fellows of the Royal Australasian College of Surgeons in August 2020. A single reminder email followed this 2 weeks later. Mixed methods analysis was performed of the survey data. Results: There were 683 (12.3%) complete responses. Telehealth (telephone or video‐link) consultations were undertaken by 638 (85%) respondents as a result of the pandemic, with 583 (85%) of these expressing a desire for continued access to telehealth. Seventy‐seven percent of respondents felt that a satisfactory level of care could be delivered via telehealth in half or more consultations. However, only 38% of respondents felt that quality of care was equivalent comparing telehealth and face‐to‐face consultations, with the inability to perform a clinical examination a frequent concern. The majority agreed that telehealth was appropriate for clinical meetings and arranging investigations (91% each), whereas only 22% and 17%, respectively, felt telehealth was an appropriate means to break bad news and manage conflict. Medicolegal, technical and financial concerns were raised as prominent barriers to the sustained use of telehealth. Conclusion: Surgeons show good insight into the clinical appropriateness and limitations of telehealth. Medicolegal, technical and financial barriers need to be addressed in order to fully utilize the benefits of telehealth into the future. Abstract : The COVID‐19 pandemic has brought the rapid and widespread introduction of Telehealth to surgery. These survey results suggest that many surgeons have utilized telehealth and wish to continue its use into the future. Clinical appropriateness, technical, medicolegal and financial issues need to be addressed for the sustained integration of telehealth into surgical care in Australia.